Sansberry Enterprise / Abd Aziz Khairullah Suhaimi ... [et al.] - Suhaimi, Abd Aziz Khairullah; Abdullah, Nursyakilla; Amat, Mohd Najib; Othman, Muhammad Syafiq Hazwan (2011)
SANSBERRY Enterprise provides enterprises in the cultivation of strawberries and manufacturing them into various products including foods and beverages and we are focusing into Sabah and Sarawak market. The idea behind the business is to provide healthy foods for consumers and to develop varieties of strawberries. Besides that, we observed that the demand are increasing from time to time but the supplies are still lacking and we are in the opinion to fill the vacant. Our company is more towards manufacturing rather than retail. We are going to cultivate strawberries then manufacturing them into various products also supplied them to another company. Strawberries can be cultivated commercially or using the hydrophonic system. Our company are to use the hydroponic system as it need less space and time to grow, produce year round yields and consistent strawberries as it is not seasonal dependent, produce strawberries of excellent taste and size where they get enough nutrients, save more cost on fertilizer as organic fertilzer can be used, promotes nearly non-existent of pests, weeds and diseases by using methyl bromide also act as a threat to the Nature as it is proven to be ecofriendly and does not support the greenhouse effect. We have chosen to cultivate the Strawberry ( Fragaria ananassa ). It is one of the most fascinating fruits of the world which is rich in vitamins and minerals. It has fabulous flavor and aroma. For maximum growth, nutrient solution of pH between 5.8-6.2 will be used. Strawberries usually cultivated in places of low temperature and cool climate of 10 to 20 degree celsius. Highlands may be the most suitable place for cultivating strawberries with a height more than 1500 metres. The reason for selecting this business depends on the business opportunity where they are suitable weather here in Malaysia, the demand are significantly increasing and the market is spreading, it gradually growing its variety and half of the demand are from the local supplies. There is opportunity for this industry. The current market demand is about 300 tonnes where 66.6% are imported and only small percentage are supplied by the local producers. The number of exports are still small. Even the largest strawberry producers in the world, China, only manage to exports 203 metric tonnes out of 1.5 million metric tonnes and the largest buyer is Russia accounting for about 90%. That is why we are looking forward to open and expand this business thus, to be as good as China but of course still we are focusing in Sabah and Sarawak first. ln the near future, it is very much possible to decrease the imports of Malaysia and increase the export after meeting the local demand.